PEMETAAN ZONASI DAERAH RAWAN KEBAKARAN HUTAN DAN LAHAN DI KABUPATEN GOWA - Yuliandri Pualilin; Amir Tjoneng; Abdullah Abdullah (Percetakan Umi Toaha Makassar, 2019)
Recent forest and land fires often occur, Gowa district has become a subscription to forest and land fires every time it enters the dry season. The research aims to determine the factors that influence forest and land fires, the distribution of areas prone to forest and land fires, compile / make zoning maps of areas prone to forest fires and in Gowa Regency. This research was conducted in Gowa Regency from April to July 2018. This study used software Arc GIS software to map areas prone to forest and land fires in Gowa Regency. The method used in this study is scoring and weighting by calculating the numerical index of the area prone to forest fires based on vegetation parameters, slope, slope direction (aspect), distance from the road, and distance from the settlement. The results of the study showed that Gowa Regency was dominated by classes of vulnerable forest fires and low land with medium to wide area of 68,777.43 hectares and 70,132.79 hectares. The causes of forest and land fires that have the potential to cause forest and land fires are land cover, slope and aspect. Areas prone to forest and land fires are the most potential to occur in Parangloe, Tombolopao, Bungaya, Bontolempangan, Biringbulu, Manuju and Pattallassang sub-districts with a total area of 1,735.42 ha or 0.96% of the total area of Gowa Regency, while areas prone to forest fires and the smallest land occurred in Pallangga District with an area of 0.24 Ha.